1995
DOI: 10.1093/infdis/171.6.1559
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Human Bronchoalveolar Macrophages and Blastomyces dermatitidis Conidia: Demonstration of Fungicidal and Fungistatic Effects

Abstract: The effects of human bronchoalveolar macrophages (BAMs) on Blastomyces dermatitidis conidia were investigated. Macrophage monolayers were incubated for 5 days with or without interferon (IFN)-gamma or macrophage colony-stimulating factor (M-CSF) before challenge with conidia for 48 h at 37 degrees C. Hyphal growth (germination) was inhibited 12% by resident BAMs (P < .05). In contrast, resident BAMs blocked conidial phase transition by 88% (P < .05). Intermediate forms, aggregates of large cells in clums (not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Similarly, in rat alveolar macrophages, IFN-1' has been demonstrated to suppress phagocytosis and induce the intracellular growth of M. avium complex (21). Sugar and colleagues (22) found that IFN-'Y reduced the capacity of human alveolar macrophages to inhibit phase transition of Blastomyces dermatidis. While the role of IFN-')'…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in rat alveolar macrophages, IFN-1' has been demonstrated to suppress phagocytosis and induce the intracellular growth of M. avium complex (21). Sugar and colleagues (22) found that IFN-'Y reduced the capacity of human alveolar macrophages to inhibit phase transition of Blastomyces dermatidis. While the role of IFN-')'…”
Section: Discussionmentioning
confidence: 99%
“…In the lung, alveolar macrophages and neutrophils can kill conidia; however, under experimental conditions, not all conidia are killed. 75,76 Conidia that survive the innate immune defenses can germinate as yeast. 55 Yeasts are more difficult to kill by host cells because they inhibit host cell cytokine production, impair CD4 þ T lymphocyte activation, are relatively resistant to reactive oxygen species (ROS), and actively suppress nitric oxide (NO) production.…”
Section: Host Responsementioning
confidence: 99%
“…The signature Th1 cytokine, IFN-g, manifests pleotropic effects on immune cells during infection. It induces classical activation of macrophages that is critical for arresting growth of intracellular fungal pathogens including H. capsulatum, B. dermatitidis, P. brasiliensis, and Coccidioides immitis (Beaman 1987;Brummer and Stevens 1995;Sugar et al 1995;Calvi et al 2003). These classically activated phagocytes are speculated to mediate their fungicidal activities through the release of nitric oxide and reactive oxygen intermediates ).…”
Section: Th1 Immunitymentioning
confidence: 99%